The Effectiveness of a Serious Game (MemoreBox) for Cognitive Functioning Among Seniors in Care Facilities: Field Study - Jana Marina Kleschnitzki; Luzi Beyer; Reinhard Beyer; Inga Großmann (JMIR Publications, 2022)
BackgroundSerious games have been found to have enhancing and preventative effects on cognitive abilities in healthy older adults. Yet, there are few results on the effects in older seniors with age-related low cognitive impairments. Their special needs were considered when designing and using innovate technology in the area of prevention, which is especially relevant owing to the continuously aging population. ObjectiveThe objective of this study was to evaluate the impact of a serious game on the cognitive abilities of seniors in order to potentially implement innovative resource-oriented technological interventions that can help to meet future challenges. MethodsIn this controlled trial, we tested the serious game MemoreBox, which features modules specifically designed for seniors in nursing homes. Over a period of 1 year, we tested the cognitive abilities of 1000 seniors at 4 time points using the Mini-Mental Status Test. Only half of the participating seniors engaged with the serious game. ResultsThe study included an intervention group (n=56) and a control group (did not play; n=55). Based on the in-game data collection, a second intervention group (n=38) was identified within the original intervention group, which exactly followed the planned protocol. There were no noteworthy differences between the demographic and main variables of the overall sample. The large reduction in the sample size was due to the effects of the COVID-19 pandemic (drop-out rate: 88.9%). The CI was set at 5%. Mixed analysis of variance (ANOVA) between the cognitive abilities of the intervention and control groups did not show a statistically significant difference between time and group (F2.710,295.379=1.942; P=.13; partial η²=0.018). We noted approximately the same findings for mixed ANOVA between the cognitive abilities of the second intervention and control groups (F3,273=2.574; P=.054; partial η²=0.028). However, we did observe clear tendencies and a statistically significant difference between the 2 groups after 9 months of the intervention (t88.1=−2.394; P=.02). ConclusionsThe results of this study show similarities with the current research situation. Moreover, the data indicate that the intervention can have an effect on the cognitive abilities of seniors, provided that they regularly play the serious game of MemoreBox. The small sample size means that the tendency toward improvement cannot be proven as statistically significant. However, the tendency shown warrants further research. Establishing an effective prevention tool as part of standard care in nursing homes by means of an easy-to-use serious game would be a considerable contribution to the weakened health care system in Germany as it would offer a means of activating senior citizens in partially and fully inpatient care facilities. Trial RegistrationGerman Clinical Trials Register DRKS00016633; https://tinyurl.com/2e4765nj